Effects of Fixed Minidose Warfarin on Coagulation and Fibrinolysis Following Major Gynaecological Surgery - MacCallum, P K; Thomson, J M; Poller, L (Thrombosis and Haemostasis, 1990)
Coagulation and fibrinolytic studies have been performed in patients who were undergoing major gynaecological surgery and randomised to either fixed minidose warfarin (1 mg daily) or matched placebo. With warfarin, a prolongation of the prothrombin time was observed on day 2 which persisted for at least 5 days and was greater than with placebo. The maximal postoperative mean INR was, however, only 1.2 which is considerably less than the target value for prophylaxis of deep vein thrombosis with full dose warfarin. The warfarin group showed two unexpected findings: significantly elevated fibrin specific degradation products throughout the postoperative period compared with placebo and absence of the expected rise of PAI, the major fibrinolytic inhibitor, on the first day after surgery. Levels of fibrinogen degradation products and FI + 2 prothrombin fragments rose significantly and progressively in both groups in the postoperative period. With placebo, FI + 2 showed an apparent higher percentage increase on each post-operative day but the differences between the groups were not significant. Increased fibrinolysis may be one of the mechanisms for the protective action of minidose warfarin in prophylaxis of DVT after major surgery.